Averaging method in multifrequency systems with delay - Bigun, Ya. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We justify the averaging method for systems with delay that pass through resonances in the process of evolution. We obtain an estimate of the error of the method that explicitly depends on a small parameter.